Associative Learning of Stimuli Paired and Unpaired With Reinforcement: Evaluating Evidence From Maggots, Flies, Bees, and Rats - Schleyer, Michael; Fendt, Markus; Schuller, Sarah; Gerber, Bertram (Frontiers in Psychology, 2018)
Finding rewards and avoiding punishments are powerful goals of behavior. To maximize reward and minimize punishment, it is beneficial to learn about the stimuli that predict their occurrence, and decades of research have provided insight into the brain processes underlying such associative reinforcement learning. In addition, it is well known in experimental psychology, yet often unacknowledged in neighboring scientific disciplines, that subjects also learn about the stimuli that predict the absence of reinforcement. Here we evaluate evidence for both these learning processes, with the aim of drawing attention to the implications of these findings for understanding the neuronal mechanisms of associative learning, and for designing ‘control’ procedures for it. We focus on two study cases that employ different kinds of control procedure: one aiming at preventing the establishment of associative memory, the other at preventing its behavioral expression. Both strategies provide a baseline level of behavior against which the effects of associative learning can be assessed. Firstly, a re-analysis of the literature on Drosophila larvae reveals that through paired presentations of an odor and a reward the animals learn that the reward can be found where the odor is. In contrast, through unpaired training the animals learn that the reward can be found precisely where the odor is not. In addition, we present previously unpublished data demonstrating that also during a two-odor, differential conditioning protocol both these learning processes take place in larvae, i.e. learning about both the rewarded stimulus and the non-rewarded stimulus. Secondly, after briefly discussing published evidence from adult Drosophila, honeybees, and rats, we report an unpublished data set showing that rats exhibit memories of opposite valence upon paired and unpaired training. Collectively, the evidence conforms to classical findings in experimental psychology and suggests that across species animals associatively learn both through paired and through unpaired presentations of stimuli with reinforcement – with opposite valence. While the brain mechanisms of unpaired learning for the most part still need to be uncovered, the immediate implication is that using unpaired procedures as a mnemonically neutral control for associative reinforcement learning may be leading analyses astray.